Wound myiasis: the role of entodermoscopy - João Renato Vianna Gontijo; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Although wound or traumatic myiasis is common in tropical countries, only recently cases associated with underlying dermatoses, such as seborrheic dermatitis and psoriasis, have been reported. We describe a patient with seborrheic dermatitis and an ulcerated lesion on the scalp, in which the dermatological examination with the aid of dermoscopy allowed the identification of larvae (maggots) compatible with infestation by Cochliomyia hominivorax. Treatment was performed with oral and topical ivermectin, followed by manual extraction of the larvae.